2005
DOI: 10.1111/j.1479-828x.2005.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hyoscine‐N‐butyl bromide (Buscopan) suppositories as a cervical spasmolytic agent in labour

Abstract: Hyoscine-N-butyl bromide (HBB, Buscopan) suppositories were highly effective in shortening the duration of the first stage of labour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 3 publications
10
45
2
2
Order By: Relevance
“…That HBB can be used as a cervical spasmolytic has been evaluated in many studies, [3,4,[6][7][8][9] and the results corroborated with our study. Bhattacharya et al, [4] studied the effect of 20 mg HBB intramuscularly on 100 primigravidas and found that mean labor time was shortened by 3 hours 40 minutes and 81% delivered within 8 hours.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…That HBB can be used as a cervical spasmolytic has been evaluated in many studies, [3,4,[6][7][8][9] and the results corroborated with our study. Bhattacharya et al, [4] studied the effect of 20 mg HBB intramuscularly on 100 primigravidas and found that mean labor time was shortened by 3 hours 40 minutes and 81% delivered within 8 hours.…”
Section: Discussionsupporting
confidence: 82%
“…[9] The advantages of intravenous route in a controlled manner (slow i/v over 1-2 minutes) are its rapid onset of action and bypass of hepatic metabolism. The rectal route is also popular [8] for this reason.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chan et al did not find an impact of hyoscine butylbromide on the duration of first stage of labour whereas Sirohiwal et al have found that hyoscine N-butyl bromide suppositories have a significant reducing effect on the first stage of labour. 21,22 Samuels et al too showed a similar reducing effect of hyoscine butylbromide on the mean duration of first stage of labour against a placebo. 23 Raghavan et al in a comparative assessment of hyoscine butyl-bromide with valethamate bromide against a placebo showed a significantly better efficacy in both the test groups in acceleration of first stage of labour.…”
Section: Discussionmentioning
confidence: 90%
“…In different studies hyoscine butylbromide and drotaverine hydrochloride have independently shown controversial results Chan et al 11 did not find an impact of hyoscine butylbromide on the duration of first stage of labor whereas Sirohiwal et al 12 have found that hyoscine N-butylbromide suppositories have a significant reducing effect on first stage of labor. Samuels et al 13 too showed a similar reducing effect of hyoscine butylbromide on the mean duration of first stage of labor against a labor.…”
Section: Discussionmentioning
confidence: 98%